Multilayer omics reveals the molecular mechanism of early infection of Clonorchis sinensis juvenile - Yuhong Wu; Xueling Deng; Zhanshuai Wu; Dengyu Liu; Xiaoyin Fu; Lili Tang; Shanshan He; Jiahui Lv; Jilong Wang; Qing Li; Tingzheng Zhan; Zeli Tang (Parasites & Vectors, 2023)
Abstract Background Clonorchiasis remains a non-negligible global zoonosis, causing serious socioeconomic burdens in endemic areas. Clonorchis sinensis infection typically elicits Th1/Th2 mixed immune responses during the course of biliary injury and periductal fibrosis. However, the molecular mechanism by which C. sinensis juvenile initially infects the host remains poorly understood. Methods The BALB/c mouse model was established to study early infection (within 7 days) with C. sinensis juveniles. Liver pathology staining and observation as well as determination of biochemical enzymes, blood routine and cytokines in blood were conducted. Furthermore, analysis of liver transcriptome, proteome and metabolome changes was performed using multi-omics techniques. Statistical analyses were performed using Student's t-test. Results Histopathological analysis revealed that liver injury, characterized by collagen deposition and inflammatory cell infiltration, occurred as early as 24 h of infection. Blood indicators including ALT, AST, WBC, CRP and IL-6 indicated that both liver injury and systemic inflammation worsened as the infection progressed. Proteomic data showed that apoptosis and junction-related pathways were enriched within 3 days of infection, indicating the occurrence of liver injury. Furthermore, proteomic and transcriptomic analysis jointly verified that the detoxification and antioxidant defense system was activated by enrichment of glutathione metabolism and cytochrome P450-related pathways in response to acute liver injury. Proteomic-based GO analysis demonstrated that biological processes such as cell deformation, proliferation, migration and wound healing occurred in the liver during the early infection. Correspondingly, transcriptomic results showed significant enrichment of cell cycle pathway on day 3 and 7. In addition, the KEGG analysis of multi-omics data demonstrated that numerous pathways related to immunity, inflammation, tumorigenesis and metabolism were enriched in the liver. Besides, metabolomic screening identified several metabolites that could promote inflammation and hepatobiliary periductal fibrosis, such as CA7S. Conclusions This study revealed that acute inflammatory injury was rapidly triggered by initial infection by C. sinensis juveniles in the host, accompanied by the enrichment of detoxification, inflammation, fibrosis, tumor and metabolism-related pathways in the liver, which provides a new perspective for the early intervention and therapy of clonorchiasis. Graphical Abstract